Initial surgery versus conservative management of chronic severe aortic regurgitation in mild symptomatic older patients - Mijin Kim; Ha Hye Jo; Sahmin Lee; Byung Joo Sun; Ho Jin Kim; Joon Bum Kim; Sung-Ho Jung; Jong-Min Song; Dae-Hee Kim (International Journal of Cardiology: Heart & Vasculature)
Background: Aortic valve replacement (AVR) for severe aortic regurgitation (AR) should be weighed against its operative risk. Mortality is lower in patients with mild symptoms than in those with severe symptoms, while the surgical risk remains high in older patients. This study aimed to evaluate the survival benefit of AVR in mildly symptomatic older patients with severe AR. Methods: From 1996 to 2016, we evaluated 127 older patients with severe AR and mild symptoms. We compared all-cause and cardiac mortality between patients who underwent AVR (OP group, n = 35) and those who were conservatively managed (CONV group, n = 92). Results: Although patients in the OP group were younger than those in the CONV group (74.2 ± 3.2 vs. 77.3 ± 5.2, p = 0.003), no differences were observed in the Society of Thoracic Surgeons score (1.93 ± 0.95 vs. 2.51 ± 1.8, p = 0.12), comorbidity, indexed left ventricular dimensions (LVEDDi: 41.3 ± 4.4 vs. 41.6 ± 5.9 mm/m2, p = 0.80; LVESDi 30.7 ± 4.6 vs. 30.6 ± 5.2 mm/m2, p = 0.90), and ejection fraction (46.7 ± 9.9 % vs. 46.9 ± 7.9 %, p = 0.89). Over a median follow-up of 4.2 years, the OP group had significantly lower all-cause (22.9 % vs. 62.0 %, p = 0.010) and cardiac mortality (8.6 % vs. 33.7 %, p = 0.019). In multivariate Cox analysis, AVR remained independently associated with reduced all-cause (HR 0.41; 95 % CI 0.19–0.90; p = 0.027) and cardiac mortality (HR 0.29; 95 % CI 0.09–0.99; p = 0.048). Conclusion: In mildly symptomatic older patients with severe AR, AVR significantly reduced all-cause and cardiac mortality and should not be withheld solely due to age.